Advancing point-of-care testing with nanomaterials-based screen-printing electrodes - Sophia Nazir (Sensors International)
Although numerous studies have been conducted on multiple screen-printing electrodes (SPEs), little emphasis has been placed on systematically assessing scholarly work on nanomaterial-equipped SPEs in bioanalytical research. The fabrication of state-of-the-art portable screen-printing measuring devices represents significant disease monitoring and diagnosis advancements. This review classifies screen-printing electrodes based on the nanomaterials used. It discusses cost, regulatory approvals for portable screen-printing electrodes in point-of-care diagnostics, sensitivity, specificity, size reductions, and proposed solutions. It looks into the significance of new nanomaterials and substrates in fabricating point-of-care diagnostic devices and miniaturisation techniques. The review primarily focuses on the recent downsizing advances that have resulted in a growing number of portable screen-printing electrodes for quick point-of-care diagnostics. Special attention is given to identifying different bioanalytics associated with distinct medical problems. Screen-printing biosensors potentially transform healthcare by allowing for rapid, accurate, and individualised diagnosis. These biosensors improve disease management, medical outcomes, and global diagnostic accessibility as technology advances.